Bidentate organochalcogen ligands (N, E; E = S/Se) as stabilizers for recyclable palladium nanoparticles and their application in Suzuki–Miyaura coupling reactions. (1st October 2019) - Sharma, Pratibha; Arora, Aayushi; Oswal, Preeti; Rao, G.K.; Kaushal, Jolly; Kumar, Sushil; Kumar, Satyendra; Singh, M.P.; Kumar Singh, Ajai; Kumar, Arun
Graphical abstract: Easily synthesizable, air and moisture insensitive, stabilizers with soft (S/Se) and hard (N) donors for catalytically active and recyclable Pd(0) NPs. High activity of NPs for catalyzing Suzuki coupling of aryl halides in short reaction time. Recyclability of nanocatalysts due to balance between their stability and activity. Abstract: Chalcogeno-substituted secondary aminesL1 andL2 have been synthesized by the reduction of corresponding imines. LigandsL1 andL2 have been characterized using 1 H and 13 C 1 H NMR spectroscopy. The Schiff base precursors used for the synthesis ofL1 has also been characterized using single crystal x-ray diffraction technique. Both the ligands (L1 andL2 ) have been used as stabilizers for palladium nanoparticles (PdNPs)1 –4 in two different ratios of Pd:L (1:1 and 1:4). The NPs have been characterized by UV–Vis spectroscopy, powder X-ray diffraction, scanning electron microscopy (SEM), SEM-EDX, and transmission electron microscopy (TEM). The chalcogen donor site showed remarkable role in the stabilization of these nanoparticles. The Pd:L ratio in NPs has been noticed to affect the size and shape of particles and also their catalytic behavior. Size of the NPs has been found to be in a range of 2–3 nm (NPs1 ); 4–5 nm (NPs2 ); 3–4 nm (NPs3 ); and 4–6 nm (NPs4 ). When explored as catalyst, the low loading of these NPs gave significant conversions for the coupling of various aryl halides with phenylboronic acid (Suzuki–Miyaura coupling) in a short reaction time of 3 h. The highest catalytic activity has been observed for Pd NPs1 (Pd:L ratio 1:1) due to the uniformity in the dispersion of particles. The distinct advantage associated with these NPs (1 –4 ) is that they retain catalytic activity after the reaction and are recyclable up to three times. Attempts were made to gain mechanistic insights of catalysis and it was found that both homogeneous and heterogeneous catalytic processes contribute to the catalysis.